Surgical Treatment of Idiopathic Macular Hole Using Different Types of Tamponades and Different Postoperative Positioning Regimens - M. Veith; J. Vránová; J. Němčanský; J. Studnička; M. Penčák; Z. Straňák; P. Mojžíš; P. Studený; D. P. Piñero (Journal of Ophthalmology)
Purpose. To compare the effect of different types of intraocular tamponade and different types of postoperative positioning on the closure of idiopathic macular hole (IMH). Methods. Prospective randomized clinical trial enrolling 104 eyes of 100 patients (age, 57–87 years) undergoing MH surgery. All patients were operated on by an experienced surgeon using 25-gauge pars plana vitrectomy (PPV) and internal limiting membrane (ILM) peeling. Patients were randomized according to the type of intraocular tamponade and postoperative positioning into the following four groups: SF6 + nonsupine reading position (n = 26) (group 1), air + nonsupine reading position (n = 25) (group 2), air + prone position (n = 26) (group 3), or SF6 + prone position (n = 27) (group 4). The follow-up period was 6 months. Results. MH closure was achieved in 87 eyes (83.7 %) in the overall sample after the first surgery, with closure rates of 100%, 56%, 84.6%, and 92.6% in groups 1, 2, 3, and 4, respectively. The group 2 was significantly less successful compared to the other three groups (p < 0.05). MH of sizes ≤400 µm was closed in 97.2% of cases after the first surgery, with no significant differences between groups (p = 0.219). MH with sizes over 400 µm was closed in 70.9% of cases after the first surgery, with both groups with air tamponade being significantly less successful than group 1. The nonsupine reading position was subjected to a better subjective evaluation in terms of postoperative comfort and quality of sleep, with no differences between air and SF6 tamponade tolerance. Conclusion. PPV with ILM peeling, intraocular tamponade, and positioning remains the basic surgical approach in the treatment of IMH. For MH ≤ 400 µm, a high closure rate can be achieved by combining air tamponade and nonsupine reading position. For macular holes >400 µm, the greatest anatomical success can be achieved by using the SF6 tamponade in combination with the nonsupine reading position.